If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -25 = 90 + -2x Reorder the terms: -25 + Y = 90 + -2x Solving -25 + Y = 90 + -2x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + Y = 90 + 25 + -2x Combine like terms: -25 + 25 = 0 0 + Y = 90 + 25 + -2x Y = 90 + 25 + -2x Combine like terms: 90 + 25 = 115 Y = 115 + -2x Simplifying Y = 115 + -2x
| -7.7m+19.59=13.11-15.8m | | 2x+44=3 | | 16-5(3x+2y)= | | 122x^2+11x-15= | | 9*100-1000= | | 2(7x+2)=5x | | -3(5y-7)+2(3y+9)= | | 2x(3x+1)=5x+7 | | 5x-4=2(3x+2) | | 9p+10=p | | 7x(x-4)=5x(x-2) | | 0.5x+2+0.5x=12-3x | | p-4=-9+p+5 | | -7.3n-6.03+4.8n=-3.7n-18.51 | | 3x^2+12=-30 | | 0.5x+2+0.5=12-3x | | -(v+17)=5(v-3) | | 48*2-4= | | 4y+3z=74 | | 3x(2x-1)=2x+13 | | 280=2(2w-4)+2w | | 15x+20x=16 | | -5m+10=5(2-m) | | 12.7-18.5+15+6.3-1+28.5=x | | 3(x+3)-10(x+1)=0 | | 5ln(4x+4)=28 | | 8x+10=2+x+4 | | 11-(x+8)=7x-5 | | 3x(x-6)=2x(x-7) | | 4x=9-2x | | 2x-4=9+x | | (84-2x)(70+5x)=y |